Dissociated Fear and Spatial Learning in Mice with Deficiency of Ataxin-2 - Huynh, Duong P. (Public Library of Science, 2009)
Mouse models with physiological and behavioral differences attributable to differential plasticity of hippocampal and amygdalar neuronal networks are rare. We previously generated ataxin-2 (Atxn2) knockout mice and demonstrated that these animals lacked obvious anatomical abnormalities of the CNS, but showed marked obesity and reduced fertility. We now report on behavioral changes as a consequence of Atxn2-deficiency. Atxn2-deficiency was associated with impaired long-term potentiation (LTP) in the amygdala, but normal LTP in the hippocampus. Intact hippocampal plasticity was associated behaviorally with normal Morris Water maze testing. Impaired amygdala plasticity was associated with reduced cued and contextual fear conditioning. Conditioned taste aversion, however, was normal. In addition, knockout mice showed decreased innate fear in several tests and motor hyperactivity in open cage testing. Our results suggest that Atxn2-deficiency results in a specific set of behavioral and cellular disturbances that include motor hyperactivity and abnormal fear-related behaviors, but intact hippocampal function. This animal model may be useful for the study of anxiety disorders and should encourage studies of anxiety in patients with spinocerebellar ataxia type 2 (SCA2).